Intra-Abdominal Heterotopic Cardiac Xenotransplantation: Pearls and Pitfalls - DiChiacchio, Laura; Singh, Avneesh K.; Chan, Joshua L.; Shockcor, Nicole M.; Zhang, Tianshu; Lewis, Billeta G.; Ayares, David; Corcoran, Philip; Horvath, Keith A.; Mohiuddin, Muhammad M. (Frontiers in Cardiovascular Medicine, 2019)
Heterotopic cardiac xenotransplantation in the intra-abdominal position has been studied extensively in a pig-to-baboon model to define the optimal donor genetics and immunosuppressive regimen to prevent xenograft rejection. Extensive investigation using this model is a necessary stepping stone toward the development of a life-supporting animal model, with the ultimate goal of demonstrating suitability for clinical cardiac xenotransplantation trials. Aspects of surgical technique, pre- and post-operative care, graft monitoring, and minimization of infectious risk have all required refinement and optimization of heterotopic cardiac xenotransplantation over time. This review details non-immunologic obstacles relevant to this model described by our group and in the literature, as well as strategies that have been developed to address these specific challenges.